Analisis Problematika Guru dalam Pembelajaran Daring pada Pembelajaran Tematik di SD/MI - Nila Nila; Lathifah Abdiyah; Agus Dwi Prasojo (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2021)
This study aims to explain the problems of online learning for teachers in improving thematic learning in SD/MI during online learning. The research method used in this study is a qualitative research method. Based on the object of study, this research is a literary research or library research. Library research is a research conducted by collecting data, information, and various other data contained in the library. Sources of data used in this study are books, journals, articles, and other scientific works that are relevant to the object of study in this study. The results of the study show that the problems of online learning have an impact on teachers and explain online learning in thematic learning and its problems.